Designing and Validating an Educational Package Based on the Lived Experiences of Mothers of Children with High-Functioning Autism Spectrum Disorder and Its Effectiveness on Parental Self-Efficacy - Rahman, Ali; Ashayeri, Hassan; Dolatabadi, Shiva; Ebrahimipour, Majid (Iranian Journal of Neurodevelopmental Disorders, 2027)
Purpose: The present study aimed to design and validate an educational package based on the lived experiences of mothers of children with high-functioning autism spectrum disorder and to examine its effectiveness on parental self-efficacy. Methods and Materials: This applied study used an exploratory sequential mixed-methods design. In the qualitative phase, a qualitative research method based on grounded theory was used to explore the deep lived experiences of mothers of children with high-functioning autism spectrum disorder. In the quantitative phase, a quasi-experimental pretest–posttest design with a control group and a three-month follow-up was employed. The statistical population in both qualitative and quantitative phases consisted of all mothers of children with high-functioning autism spectrum disorder who had referred to autism centers in Tehran during the second half of 2024. In the qualitative phase, 15 mothers were selected through purposive sampling. In the quantitative phase, according to the inclusion criteria, 30 mothers were selected through purposive sampling and then randomly assigned to an experimental group and a control group, with 15 participants in each group. Data were collected using library and field methods. The quantitative data were gathered using the Domka Parental Self-Efficacy Scale (1996). The researcher-made parent–child challenge-based parenting educational package was implemented for the experimental group in twelve 90-minute sessions. Qualitative data were analyzed through open, axial, and selective coding, and quantitative data were analyzed using repeated-measures analysis of variance in SPSS version 26. Findings: The qualitative findings showed that seven factors played a role in developing the effectiveness of the parenting educational program: family factors, economic factors, environmental factors, social factors, educational approach, psychological approach, and psychological consequences. Based on the extracted components from mothers’ lived experiences, the educational package was developed in 12 sessions, and the findings indicated satisfactory validity. In the quantitative phase, the results showed that the parent–child challenge-based educational package had a significant effect on parental self-efficacy, explaining 51% of its variance (p < .01). Conclusion: It can be concluded that an educational intervention based on mothers’ lived experiences can enhance parental self-efficacy, and its positive effects may remain observable and stable in the medium term.